2016
DOI: 10.1002/macp.201500510
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor Reversible Thermochromic Properties of Gallic Acid-Cored Polydiacetylenes Appended with Poly(alkyl aryl ether) Dendrons

Abstract: This study describes synthesis of zero and fi rst generation poly(alkyl aryl ether) dendrons onto a gallic acid core, tethered with three diacetylene moieties and their photopolymerization. Resulting polydiacetylenes are studied by (i) UV-vis, IR, Raman spectroscopies, and chromoisomerism by naked eye visualization; (ii) their stabilities by differential scanning calorimetry, thermogravimetric method, and (iii) structure, morphology, and emission behavior by scanning electron, transmission electron, atomic for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…When the carboxylic group of the garlic acid was replaced with poly(alkyl aryl ether) dendrons to obtain monomer 2, the reversible thermochromism was further improved to 300 °C, as a result of enhanced interactions provided by the dendrons. 326 Alternatively, a linker was used to attach two α-D-mannopyranoside moieties at the position of the carboxylic group of the gallic acid to obtain monomer 5 that can be used for sensing, i.e., to assess the carbohydrate−protein interaction between sugar and lectin via chromic changes. It was found that the addition of the lectin concanavalin A (Con A) to PDA vesicles made from these monomers did not induce a color change of the system, even though DLS and AFM clearly showed an increase in the size of the vesicles.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…When the carboxylic group of the garlic acid was replaced with poly(alkyl aryl ether) dendrons to obtain monomer 2, the reversible thermochromism was further improved to 300 °C, as a result of enhanced interactions provided by the dendrons. 326 Alternatively, a linker was used to attach two α-D-mannopyranoside moieties at the position of the carboxylic group of the gallic acid to obtain monomer 5 that can be used for sensing, i.e., to assess the carbohydrate−protein interaction between sugar and lectin via chromic changes. It was found that the addition of the lectin concanavalin A (Con A) to PDA vesicles made from these monomers did not induce a color change of the system, even though DLS and AFM clearly showed an increase in the size of the vesicles.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…Sugar ligands attached polydiacetylenes are known to undergo changes in the chromatism as a result of the ligand‐receptor interactions [42–44] . A facile formation of vesicles occurs with such ligand‐tethered polymers [44–48] . The chemical structures of glycolipid M‐L , lipid E‐L and the corresponding polymeric mixed vesicles studied herein are shown in Figure 1, synthesis and characterization are given in the Supporting Information (Section S1).…”
Section: Resultsmentioning
confidence: 99%
“…Polymers form stable glycovesicles in a facile manner in aqueous solutions. Visual color changes of the glycovesicles upon interaction with the protein lead to derive colorimetric ratio, which defines the extent with which the polydiacetylene functionality undergoes perturbation as a result of the receptor interaction [48–53] …”
Section: Resultsmentioning
confidence: 99%